TUAH: Malaysia marine combat boat / Mohd Danish Mohd Faizal - Mohd Faizal, Mohd Danish (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
TUAH is a combat boat designed for the Malaysian Marine Force. According to the analytical questionnaire given by the Malaysian Marine Force, Tuah is developed for the Malaysian Marine Force with an excellent modern design, ferocious and innovative with futuristic features. The issues with the current combat boat are the design of each component, as well as the components, that needed to be upgraded and also In terms of hull design, pilot deck, weapon, operating room, additional space, and engine . A descriptive survey and observations were conducted by 10 Malaysia Marine Force staff through Google Form. 90 percent of them agreed with the new initiative to redesign combat boats for the future. According to the survey, Tuah designed to look more modern with appropriate speed and full equipment for combat. It's also provided one extra space for the lookout crew. With the existence of Tuah combat boat, all operation during the mission would be much easier and thrived to succeed.